Активність 2',5'-олігоаденілатсинтетази та рівень інтерферону у лімфоцитах щурів за умов радіаційного впливу - Лаврова, К.В.; Компанець, І.В.; Остапченко, Л.І. (Вiopolymers and Cell, 2012)
Aim. To determine 2',5'-oligoadenylate synthetase (2',5'-OAS) activity and interferon (IFN) level in lymphocytes of rats irradiated with 0.25, 0.5, 0.75 and 1.0 Gy doses, as well as to study the effect of interferon inducers on these parameters. Methods. Micro method of IFN titer determination by antiviral activity testing and spectrophotometric method of 2',5'-OAS activity determination were used. Results. An increase in IFN titer in lymphocytes of rats after irradiation with 0.25 and 0.5 Gy doses was shown. Higher radiation doses of 0.75 and 1.0 Gy caused a decrease of this parameter. The 2',5'-OAS activity exceeded a control at all applied doses, the maximum level in splenocytes corresponded to 0.25 Gy dose whereas the highest values in thymocytes were revealed at 0.5-1.0 Gy doses. The IFN inducers stimulated cytokine synthesis and increased the enzyme activity in lymphocytes of irradiated rats. Conclusions. The increase of 2',5'-OAS activity and IFN titer in lymphocytes of irradiated animals may be regarded as a protective post radiation reaction of cells. Under irradiation with higher doses – 0.75 and 1.0 Gy – the studied parameters decreased, that may be associated with more serious damage of cells, for correction of which the resources of repairing systems are not enough. The increased 2',5'-OAS activity and IFN titer in lymphocytes after their pre-incubation with IFN inducers can be considered as intensification of cellular protective postradiation mechanisms.